PL.43 Cervical Compliance and Smooth Muscle. (26th April 2013) - Mowbray, C; Robson, SC; Bulmer, JN; Smith, MC
Abstract : Background: Cervical weakness is associated with late miscarriage and extreme preterm birth. Early studies reported higher cervical smooth muscle content in women who experienced second trimester loss. Contemporary studies have suggested structural composition is not related to pre-labour cervical remodelling. The aim of the present study was to explore the relationship between human cervical structure and biomechanical characteristics. Methods: Cervical biopsies were taken from 17 non-pregnant women at the time of hysterectomy. Samples were bisected longitudinally and one portion mounted on a myograph (Danish Systems). The stretch-strain characteristics were recorded using Windaq software. The non-stretched portion was fixed and immunohistologically stained with orcein (elastin) and immunostained for smooth muscle actin [SMA]. Smooth muscle and elastin content were then assessed using Photoshop image analysis. 3 biopsies were taken from each of 4 hysterectomy specimens to assess intra-subject variability. Results: The proportion of both smooth muscle and elastin content of cervical biopsies showed a wide variation (5–47% and 9–47%, SMA and elastin, respectively). Furthermore, there was considerable intra-subject variability with as much as a 2.4 fold difference in SMA content. Both SMA and elastin content correlated with biopsy compliance (R = 0.3, p < 0.01, and R = 0.4, p < 0.01 respectively). Conclusion: The biomechanical properties of human cervical biopsies are influenced by the smooth muscle and elastin content of the specimen. Histological and biomechanical characteristics of human cervical biopsies cannot be assumed to be reliably representative of the whole specimen. These findings may explain why previous studies have failed to find a relationship between biopsy characteristics and clinical history.